(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2008)
The propose investigation persecutes to study the used mechanisms of financing in the nontraditional exports of the Venezuela familiar companies; the methodology corresponds to a descriptive investigation and of field. Between the results they emphasize: little disposition to use the outsourcing of financing because it jeopardizes the control of the company into the hands of third, as far as the financial institutions demonstrated a greater use of the private sources that those of public nature, it derived from the slow capacity of answer of these. Finally, the policy of exchange control is indicated like main obstacle for the exports.